2022
DOI: 10.1021/acs.jpclett.1c04138
|View full text |Cite
|
Sign up to set email alerts
|

Size Dependence of Charge-Density-Wave Orders in Single-Layer NbSe2 Hetero/Homophase Junctions

Abstract: Controlling charge-density-wave (CDW) orders in two-dimensional (2D) crystals has attracted a great deal of interest because of their fundamental physics and their demand inse in miniaturized devices. In this work, we systematically studied the size-dependent CDW orders in single-layer hetero/homo-NbSe 2 stacking junctions. We found that the CDW orders in the top 1T-NbSe 2 layer of the junctions are highly dependent on its lateral size. For the 1T/2H-NbSe 2 heterojunction, the critical lateral size of 1T-NbSe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Two-dimensional (2D) materials have a thickness much smaller than the lateral dimension. Many of them have fascinating electronic and optoelectronic properties. 2D materials, combined with the catalyst reactions, can give rise to many advantageous applications, such as a “chainmail” catalyst, where the catalyst can be protected by the 2D materials. , However, in comparison to the extensive studies on Ullmann-like reactions on metallic substrates, few have focused on the Ullmann-like dehalogenation and coupling reaction on 2D surfaces.…”
mentioning
confidence: 99%
“…Two-dimensional (2D) materials have a thickness much smaller than the lateral dimension. Many of them have fascinating electronic and optoelectronic properties. 2D materials, combined with the catalyst reactions, can give rise to many advantageous applications, such as a “chainmail” catalyst, where the catalyst can be protected by the 2D materials. , However, in comparison to the extensive studies on Ullmann-like reactions on metallic substrates, few have focused on the Ullmann-like dehalogenation and coupling reaction on 2D surfaces.…”
mentioning
confidence: 99%
“…These two effects cooperate and become more evident in the small islands, especially when the island size is comparable to several SOD clusters. Compared to CDW melted behavior in the 1T/2H case, [18] in the SL 1T on BLG case, each SOD as a quantum unit is much more robust against the size-limiting effect. This phenomenon may be due to the SL 1T case being closer to the intrinsic free-standing case, and the doping influence from the substrate can be neglected.…”
Section: Resultsmentioning
confidence: 91%
“…From Figure 1, it is concluded that for the small 1T islands, the SOD array at the interior of the island can be still ordered, in sharp contrast to the melted CDW behavior in the 1T/2H case (Figure S1, Supporting Information). [18] After discussing the ideal triangular packing cases of small 1T-NbSe 2 islands in Figure 1, we further focus on the non-ideal cases of CDW rearrangement with robust SOD clusters. As shown in Figure 2a, there is a small island embracing six SODs in the interior, and four of them show a square-like pattern, as labeled by the red box.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transition metal dichalcogenides (TMDs), MX 2 (M = transition metal; X = S, Se, Te), have attracted increasing interest due to their different intriguing quantum states, such as superconductivity (SC) and charge density waves (CDWs). Among these materials, TaSe 2 with several phases, including 2H, 1T, and 3R, has attracted great research interest. The 2H and 1T structures both experience two CDW transitions with incommensurate and commensurate lattice contraction , and show a superconducting transition at a rather low temperature. Recently, 3R-TaSe 2 , as a very interesting structure, has been arousing wide attention as a candidate for realizing a two-dimensional superconducting system due to its higher superconducting transition temperature ( T c ) compared with bulk 2H-TaSe 2 (0.1 K) .…”
mentioning
confidence: 99%